2020
DOI: 10.1002/emp2.12102
|View full text |Cite
|
Sign up to set email alerts
|

Testing for HIV infection in the emergency departments of 2 hospitals in the Southeastern United States

Abstract: Background In 2006, the Centers for Disease Control and Prevention (CDC) recommended non‐targeted, opt‐out HIV screening in all healthcare settings, including emergency departments (EDs). Multiple HIV testing programs have been implemented in EDs across the United States with varying designs and testing platforms. We report findings from a free, non‐targeted, rapid HIV testing program in 2 EDs in the Southeastern United States. Methods From 2008 to 2012, adults ≥18 years of age were offered free rapid HIV test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Professional medical organizations and the Federal Bureau of Prisons support opt-out HCV screening for all people who are incarcerated [ 2 , 18 ]. Data from testing in emergency rooms shows increased uptake of opt-out HIV testing by Black people compared to white people [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Professional medical organizations and the Federal Bureau of Prisons support opt-out HCV screening for all people who are incarcerated [ 2 , 18 ]. Data from testing in emergency rooms shows increased uptake of opt-out HIV testing by Black people compared to white people [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Se identificaron un total de 273 artículos de los cuales 151 de ellos se excluyeron por ser registros duplicados entre las diferentes combinaciones de términos empleadas. De los 122 artículos restantes se excluyeron 110 por no cumplir con los criterios de inclusión, quedando 12 artículos (14 estudios) [12][13][14][15][16][17][18][19][20][21][22][23] . Dos artículos 20,21 aportan la información de 4 subestudios comparando dos estrategias de despistaje en dos periodos diferentes.…”
Section: Selección Y Características De Los Estudiosunclassified
“…La Tabla 1 muestra las características de los artículos incluidos. Del total de los 12 artículos publicados, 8 (66,7%) se publicaron antes del 2019, todos se realizaron en hospitales urbanos y solo uno de ellos 23 fue multicéntrico (2 centros). En relación a la región de la Figura 1.…”
Section: Selección Y Características De Los Estudiosunclassified
“…Most studies evaluating expanded HIV testing have identified new infections at rates above the 1/1,000 threshold of cost-effectiveness, implying cost savings if universally applied. 16 , 17 …”
Section: Reasons For Changing Requirements For Consentmentioning
confidence: 99%